Vapochromism associated with the changes in the molecular arrangement of organic crystals1. Issue 6 (14th February 2015) - Yamada, Shinji; Katsuki, Ayaka; Nojiri, Yuka; Tokugawa, Yoko
<x xml:space="preserve">Abstract</x> Exposure of yellow anhydrate organic crystals to water vapor gave red hydrate crystals with significant changes in the molecular arrangement.